Mendorong Minat Berwirausaha Mahasiswa Melalui Pendidikan Kewirausahaan Dan Dukungan Akademik Yang Efektif - Robbani, Ja’far; Hermana, Cecep (Jurnal Ilmiah Wahana Pendidikan, 2026)
In this era of globalization, the entrepreneurial spirit is an important key to the nation's progress. Singaperbangsa Karawang University, as a higher education institution, also contributes to fostering interest in entrepreneurship among its students. This research was conducted with the main objectives to: (1) Understand the influence of entrepreneurship education on students' interest in entrepreneurship at Singaperbangsa University, Karawang. (2) Measuring how big the role of academic support from the university is in increasing students' interest in entrepreneurship. (3) Evaluate the effectiveness of entrepreneurship programs that have been implemented by Singaperbangsa Karawang University. This research involved 100 students at Singaperbangsa University Karawang who were selected randomly (random sampling). Data was collected through a questionnaire designed to measure the variables of entrepreneurship education, academic support, and interest in entrepreneurship. Data analysis was carried out using SPSS version 23 software. This research shows that entrepreneurship education and academic support are important factors in increasing students' interest in entrepreneurship at Singaperbangsa University Karawang.